2018
DOI: 10.1016/j.soilbio.2018.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Differential capacity of kaolinite and birnessite to protect surface associated proteins against thermal degradation

Abstract: Soil organic carbon cycling depends on the presence and catalytic functionality of extracellular proteins. The mineral matrix has the capacity to enhance, maintain or impede this functionality through a variety of mechanisms. The goal of this research was to identify some of the mechanisms involved in determining the role of the mineral matrix towards proteins. To this end, we adsorbed Beta-Glucosidase (BG) and Bovine Serum Albumin (BSA) on the phyllosilicate kaolinite and the manganese oxide acid birnessite a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…6). These minerals tend to catalyze moderate changes to the structure and electronic state of adsorbed molecules, primarily through direct bonding, hydrolytic breakdown from reactions with surface OH, and heterogeneous oxidation with adsorbed O 2 123,126,127 .…”
Section: [H1] Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…6). These minerals tend to catalyze moderate changes to the structure and electronic state of adsorbed molecules, primarily through direct bonding, hydrolytic breakdown from reactions with surface OH, and heterogeneous oxidation with adsorbed O 2 123,126,127 .…”
Section: [H1] Catalysismentioning
confidence: 99%
“…6). Reduced clays (those with substituted transition metals), Mn oxides, sulfides and magnetite belong to this category 123,[127][128][129] . Mineral carbonates and sulfides, through major changes of surface acidity at the interface, play an important role in the hydrolytic breakdown of macromolecular organic molecules.…”
Section: [H1] Catalysismentioning
confidence: 99%
“…
In soils and sediments, extracellular enzymes are in contact with mineral surfaces. Minerals may (a) serve as inert sorbent surfaces (Gianfreda et al, 2011); (b) act as reactants in chemical reactions (Chacon et al, 2018); and (c) serve as catalysts (Chacon et al, 2018;Reardon et al, 2016), thus inducing alterations to the adsorbed substrate. Of particular interest are modifications in enzyme activity that may be a direct consequence of adsorption to mineral surfaces (Allison, 2006;Quiquampoix & Burns, 2007;Zimmerman & Ahn, 2010).
…”
mentioning
confidence: 99%
“…Previous studies indicated that the propensity of proteins to become cleaved increased with decreasing pH, suggesting the process might be particularly efficient in, and possibly restricted to, acidic soils and environments. When we cumulated the number of unique peptide fragments over all four time points (Figure ), the previously noted pH dependence of protein fragmentation by birnessite disappeared.…”
Section: Resultsmentioning
confidence: 99%
“…The persistence of a protein involved in a mineral association, and, by extension, its functional lifespan, are thought to be constrained by eventual microbial degradation. However, previous research demonstrated abiotic fragmentation of protein by manganese oxides, but little is known about the propensity of other relevant surface archetypes (such as negatively charged, positively charged, and predominantly neutral surfaces) to fragment a protein.…”
Section: Introductionmentioning
confidence: 99%